Challenges and opportunities to scaling smallholder mechanization in Kenya, Malawi, Zambia, and Zimbabwe - Ngoma, Hambulo; Simutowe, Esau; Md Abdul Matin; Thierfelder, Christian (International Maize and Wheat Improvement Center, 2023)
As governments heighten the drive to mechanize agriculture, critical information is required on (i) existing mechanization options, (ii) barriers and challenges, (iii) opportunities for scaling and effective demand for mechanization. This paper combines quantitative and qualitative surveys to help elucidate on some of these key issues in Kenya, Malawi, Zambia, and Zimbabwe where mechanization is part of national policy priorities. Data were collected through Qualitative surveys involving 484 participants in focus group discussions and 109 key informants. Focusing mainly on farm mechanization and irrigation options for smallholder farmers, we found that animal draft power is still dominant for land preparation, ahead of two-and four-wheel tractors. Common options for post-harvest management include shellers, improved granaries and hermetic bags. In terms of demand, there is nascent literature suggesting that farmers in Malawi, Zambia and Zimbabwe are willing to pay positive amounts for different mechanization services, indicating prevalence of effective demand and good opportunities for mechanization. Supply side barriers to scaling mechanization include limited availability of machines and spares, poor after sale, and repair and maintenance services in the vicinity of farmers. On the demand side, high capital requirements, limited awareness and technical knowledge and the high cost of hire services are some of the main barriers to scaling. Based on these findings, there is need for inclusive and innovative financing mechanisms, demand creation and awareness raising to scale up and scale out mechanization.